(untitled) (diségno, 2025)
Technological evolution has always diversified communication tools by introducing new media and languages. Digitalization demands an adaptation of codes to the immediacy required by contemporary channels, focusing attention on the word–image relationship. The acceleration of the digital transition requires a revision of communication modes, as multimedia channels interact synergistically with the sensory system, making it necessary to reconsider how words and images work together. The rhetorical principles codified for verbal language also apply to visual communication, as demonstrated by advertising, considered the “soul of commerce” due to its effectiveness in engaging the audience. The verbo-visual rhetoric of modern advertising renews the art of communication by creatively combining ethos, pathos, and logos in a narrative that appeals to emotion. In particular, Olivetti’s commercial communication channels went beyond mere product promotion. They created a syntactic–semantic ecosystem that remains relevant even in the digital era. Alongside other forms of commercial communication, advertising in general, and Olivetti’s communication in particular, serve as a reference point for updating languages in the digital age. This is especially valuable for activities operating in the virtual space as a privileged place of communication, especially in the commercial domain.